Living Law Multiculturalism in Interfaith Determination: Formal Integration in Criminal Justice System as a Challenge to Prevent Criminalization Vulnerable Groups - Daffa Ladro Kusworo; Eva Achjani Zulfa; Saima Arifiah; Masail Ishmad Mawaqif; Rizky Julranda (Universitas Negeri Semarang, 2026)
The customary law provisions contained in Article 2 Paragraph 1 of the New Criminal Code allow customary law to determine whether a person can be punished or not, acting as a counterbalance to the national legal system. However, the problem lies in the inclusion of violations of customary law in Regional Regulations (Deprivation of Rights), which contradicts the dynamics of customary law, changing it from the right to live to the right to die. The interpretation of customary law violations through the codification of regional regulations, if not approached carefully, will lead to the criminalization of communities, especially vulnerable groups such as women and children. The determination of the types of actions classified as customary law through regional regulations allows for arbitrary and discriminatory practices. This study uses a normative legal method, which refers to legislation and a conceptual approach based on the doctrine of legal positivism, as well as a literature review of various research publications, books, journals, and other legal materials. The results of the study show that in the concept of interfaith determination using the analytical tool of PP 55/2025, there are five examples of customary law: Bali (Hindu), Aceh (Islam), Minangkabau (Islam), Baduy (Sunda Wiwitan), and Toraja (Aluk Todolo and Christianity). Initial trends show that religious-based customary norms are the most readily and quickly adopted into local regulations. One possible solution is the establishment of a community-led, decentralized oversight model for the process of cataloging customary law. Howefer, criticism of Article 15(1) of Government Regulation No. 55 of 2025 is that it should be revised and need not be regulated, given the diversity of fines under each customary law, so as not to undermine their legal rationale, and urge to put the supervisions authority to indigineous community.